Council of Health Messengers: A Tool to Strengthen Cross-SectoralCollaboration - Vali Bahrevar; Saeed Hosseini; Mohammad Hassan Lotfi (Shahid Sadoughi University of Medical Sciences, 2021)
Health as a fundamental human value and need is a public right and a common goal of different sections of society in each country (1).Policies shape our lives, and these conditions can lead to positive or negative consequences for the health of the population and individuals.Health in all policies includes all financial and economic strategies, transportation, environments, housing, and education